Peningkatan Kemampuan Logika Siswa SDN 060934 melalui Game Edukasi “Lucky Box” Berbasis Multimedia - Jamaluddin, Jamaluddin; Simamora, Roni Jhonson; Ndruru, Yufita Friska; Harianja, Eva Julia G.; Purba, Eviyanti N.; Hutapea, Marlyna I.; Manalu, Darwis R.; Lumbantoruan, Gortap; Siringoringo, Rimbun; Saragih, Rijois I. E.; Nainggolan, Rena; Perangin-angin , Resianta; Napitupulu, Merry Anna (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
This community service activity aims to improve the logic skills of students at SDN 060934 through the application of multimedia-based educational games. By identifying the problems students face in understanding logic concepts, the program is designed to provide an engaging and interactive learning experience. The implementation of activities includes socialization, training, and the use of educational games that have been selected based on student needs. Evaluation results showed a significant improvement in students' logic skills, with the average pre-test score increasing from 65 to 85 in the post-test. In addition, students also reported a more enjoyable learning experience and higher motivation to learn. Although challenges related to technological infrastructure still need to be overcome, this activity proves that educational games can be effectively integrated in the learning process to support the development of critical thinking skills among students. It is recommended that this method be applied more widely in other schools in an effort to improve the quality of education in Indonesia